(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
Currently, there are possibilities for falsification of chocolate mass making, associated on the one hand with the replacement of raw materials, and on the other hand with a violation of technological processes in production. Therefore, it is necessary to improve the quality control system of incoming raw materials and the production technology.